THE PROGRAMMING LANGUAGE F# FOR THE .NET PLATFORM - SZABÓ, Tibor; SCHINDLER, Frank (Trends in education, 2009)
The aim of this article is to introduce a new programming language F# developed by the company Microsoft supporting the possibility of functional programming, object-oriented programming, declarative programming, interactive scripting and interoperability among other .NET languages. The language is still under development for the .NET platform.
Keywords: Programming language F#; programming language C#; .NET platform; object-oriented programming; functional programming; Visual Studio; Windows Forms Application.